The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.4103/1319-2442.194902
|View full text |Cite|
|
Sign up to set email alerts
|

Mineral bone disorder and its management among hemodialysis patients in the Gulf Cooperation Council: Initial findings from the dialysis outcomes and practice patterns study (2012-2015)

Abstract: The prospective cohort Dialysis Outcomes and Practice Patterns Study (DOPPS) initiated data collection in national samples of hemodialysis (HD) units (total of 41 study sites) in all six Gulf Cooperation Council (GCC) countries (Bahrain, Kuwait, Oman, Qatar, Saudi Arabia, and the United Arab Emirates) in late 2012. Here, we report initial results regarding mineral bone disorders (MBDs) and its management in the GCC countries. Forty-one randomly selected HD facilities, treating >23 HD patients each, were sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 1 publication
1
9
0
Order By: Relevance
“…Patients below the upper limit )300 pg/ml( were 23.8% )n=67(; this upper limit was reported by 71% of the centers enrolled in the DOPPS involving GCC. 9 Our sample showed a high level of parathyroid hormone )64% [n=152]( consistent with the DOPPS study, which reported high median parathyroid level in Saudi Arabia )523 pg/ml( compared to the GCC average )452 pg/ml( this results are considered higher than results in Japan and Europe. Out of patients below upper limit, 4.8% )n=13( of patients showed levels of parathyroid hormone that considered as low bone turnover and required further assessment and treatment.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Patients below the upper limit )300 pg/ml( were 23.8% )n=67(; this upper limit was reported by 71% of the centers enrolled in the DOPPS involving GCC. 9 Our sample showed a high level of parathyroid hormone )64% [n=152]( consistent with the DOPPS study, which reported high median parathyroid level in Saudi Arabia )523 pg/ml( compared to the GCC average )452 pg/ml( this results are considered higher than results in Japan and Europe. Out of patients below upper limit, 4.8% )n=13( of patients showed levels of parathyroid hormone that considered as low bone turnover and required further assessment and treatment.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, the control of serum phosphorus is considered a critical factor in improving the clinical outcomes in CKD-MBD, including survival. 8 , 9 Moreover, hyperphosphatemia represents a significant cause of morbidity and mortality in hemodialysis patients, as phosphate is not effectively removed by dialysis, the patients are required to follow a protein-restricted diet to decrease phosphate consumption. 10 Oral phosphate binders are required by the majority of patients on hemodialysis, which are agents used to control serum phosphate levels through different action mechanisms, but the net result is to prevent gastrointestinal phosphate absorption.…”
mentioning
confidence: 99%
“…The analysis described here includes data collected in the initial prevalent cross-section of patients enrolled in DOPPS phase 5 from 2012 to 2015 in 20,612 patients in 543 facilities across Europe (Belgium, France, Germany, Italy, Spain, Sweden, and the UK), Russia, Asia (China and Japan), Saudi Arabia (results for additional GCC countries have been published separately [23]), and North America (Canada and the USA). Specific parameters analyzed to assess the management of SHPT included biochemical measures and the use of SHPT medications.…”
Section: Study Design Patients and Data Collectionmentioning
confidence: 99%
“…More recently, using DOPPS phase 1–4 data (1996–2011), an iPTH elevation to > 600 pg/mL (HR 1.23) and even milder elevation of iPTH (301–450 pg/mL) were associated with mortality compared with the reference range of 150–300 pg/mL (HR 1.09) [ 22 ]. Initial findings from DOPPS phase 5 (2012–2015) in Russia and countries of the Middle East that are part of the Gulf Cooperation Council (GCC; Bahrain, Kuwait, Oman, Qatar, Saudi Arabia, and United Arab Emirates) have demonstrated variation in practices and opportunities for improvement of care [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…We were able to reveal patient characteristics on all study parameters. While existing studies in the region are limited to their descriptive and cross-sectional nature [28,29], or to their short intervention time [30], the current study is unique in its prospective interventional design implementing the IDE program in UAE.…”
Section: Discussionmentioning
confidence: 99%